(untitled) (Nudos. Revista Transdisciplinar de Sociología, Teoría y Didáctica de la Literatura, 2018)
We consider that the teaching of science consists in educate to students in experimental, procedural questions and in a relevant aspect: humanism. We will talk about classroom ethnography combining both aspects. For this, we take the galician writer Otero Pedrayo as an example and his way of seeing the world. We show, through his writings, as he used an introspective strategy. He showed a didactic approach that allows us to relate the teaching of science and language. For this reason, we propose to reflect about the importance of this inquiry at an educational level which, it could improve the training of future teachers.